2011
DOI: 10.1021/pr200725x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Apelin Peptides in Bovine Colostrum and Milk by Liquid Chromatography–Mass Spectrometry

Abstract: Apelin peptides were recently identified as endogenous ligands of the APJ receptor. It has been hypothesized that these peptides are initially provided to the newborn by nursing and might be involved in gastrointestinal tract development. As apelin peptides may have different effects on the APJ receptor as a function of their size, knowledge of their exact structure in early milk is essential to clarify their action in gastrointestinal tract development. Bovine colostrum is thought to contain high concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 29 publications
2
49
0
Order By: Relevance
“…It should be noted that this directly contrasts with an earlier HPLC-MS study where none of the expected apelin isoforms (Table 1) were detected in human plasma (Mesmin et al 2010). This latter method, however, was subsequently employed to successfully identify apelin peptides in the bovine colostrum (Mesmin et al 2011). Interestingly, in this study, many forms of apelin above and beyond the known bioactive isoforms were identified, including peptides lacking one or more Cterminal residues, to a total of 46 isoforms.…”
Section: Apelin-induced Signallingmentioning
confidence: 88%
“…It should be noted that this directly contrasts with an earlier HPLC-MS study where none of the expected apelin isoforms (Table 1) were detected in human plasma (Mesmin et al 2010). This latter method, however, was subsequently employed to successfully identify apelin peptides in the bovine colostrum (Mesmin et al 2011). Interestingly, in this study, many forms of apelin above and beyond the known bioactive isoforms were identified, including peptides lacking one or more Cterminal residues, to a total of 46 isoforms.…”
Section: Apelin-induced Signallingmentioning
confidence: 88%
“…At the early stage of cardiomyopathy, myocardial hypertrophy is a compensatory function, but ultimately, this can lead to heart failure and has become a significant independent risk factor of cardiovascular disease [47]. At present, myocardial hypertrophy occurs mainly due to mechanical load [1][2][3] and neurohumoral factors [4][5][6]. The earliest hemodynamic effect in the pathogenesis of myocardial hypertrophy has been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Several apelin peptides, such as apelin-77, apelin-36, apelin-17, apelin-13, and apelin-12, have been shown to be present in vivo, all of which have different effects on the APJ receptor due to their different sizes [2]. Apelin-13 that acts as a mature apelin peptide, is the most commonly studied and has comparable affinity and agonist activity with the native apelin receptor in human tissues [3].…”
Section: Introductionmentioning
confidence: 99%
“…7 To date, 46 different apelin peptides ranging from apelin 55 (proapelin) to apelin 12 have been identified. 8 The different forms of apelin and its receptor APJ are called apelinergic system which plays pivotal roles in the regulation of cardiovascular function, angiogenesis, fluid homeostasis, energy metabolism and stress response. 9 The apelinergic system has a widespread but selective expression in the CNS.…”
Section: Introductionmentioning
confidence: 99%